2006
DOI: 10.1246/cl.2006.390
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Formation of Ni–B Amorphous Alloy Nanoarray via Ultrasound-assisted Reductant-infiltration Strategy

Abstract: An effective and facile strategy, ultrasound-assisted reductant-infiltration, was realized in the preparation of hexagonally packed Ni–B amorphous alloy nanoarray, which exhibits superior catalytic properties to their nanoparticle counterpart in selective hydrogenation of acetophenone to 1-phenylethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The increased surface B content can invoke a stronger electronic interaction with metal (M) and higher thermal stability by impeding the migration of the metal atoms. Furthermore, Chen et al [63] synthesized a Ni-B nano-array replicated from mesoporous siliceous SBA-15. The silica-free Ni-B nano-array is constructed of hexagonally packed nanowires with a uniform diameter of about 5 nm, which exhibit superior catalytic properties to their nanoparticle counterparts in the selective reduction of acetophenone to 1-phenylethanol.…”
Section: Ultrasound-assisted Preparation Of Catalysts For Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased surface B content can invoke a stronger electronic interaction with metal (M) and higher thermal stability by impeding the migration of the metal atoms. Furthermore, Chen et al [63] synthesized a Ni-B nano-array replicated from mesoporous siliceous SBA-15. The silica-free Ni-B nano-array is constructed of hexagonally packed nanowires with a uniform diameter of about 5 nm, which exhibit superior catalytic properties to their nanoparticle counterparts in the selective reduction of acetophenone to 1-phenylethanol.…”
Section: Ultrasound-assisted Preparation Of Catalysts For Reductionmentioning
confidence: 99%
“…This catalyst exhibited superior performance in the selective reduction of acetophenone to 1-phenylethanol. [63] It was suggested that the agglomeration was inhibited by sonication wherein the surface of the catalyst becomes homogeneous and the coverage of Ni centers decreases correspondingly. Sonication also slightly increased surface area.…”
Section: Ni-catalystsmentioning
confidence: 99%
“…After that, Klabunde et al [16][17][18][19][20] and Chen et al [21][22][23][24] studied the mechanism of borohydride reduction and the relation between properties and preparation conditions. On the other hand, Deng and coworkers have been interested in studying the properties of amorphous alloy particles and the application of metal boron (MB) and metal phosphorus (MP) amorphous alloys for catalytic hydrogenation [25][26][27][28][29][30][31][32][33][34][35][36][37]. Dragieva et al focused on developing amorphous alloys as electrode or catalytic oxidation materials [38][39][40][41][42][43], while Chen and coworkers prepared MPB alloy nanoparticle catalysts for various selective hydrogenation reactions [44][45][46][47][48][49][50].…”
Section: History Of Amorphous Alloy Catalystmentioning
confidence: 99%
“…investigated widely. Klabunde et al [16][17][18][19][20], Chen et al [21][22][23][24] and Deng et al [25][26][27][28][29][30][31][32][33][34][35][36][37] have investigated the reduction mechanism thoroughly. It has been found that the mechanisms mainly depended on the types of metal ions or salts, properties of metal ions, pH values of solution and the solvent selected.…”
Section: Surface Properties Of Amorphous Alloy Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation